Anti-condensation thermal insulation coating and preparation method thereof
By leveraging the synergistic effect of the three-dimensional porous network structure of the two-component coating and the modified materials, the problems of insufficient thermal insulation and easy cracking of existing coatings have been solved. This results in coating performance that is anti-condensation, thermal insulation, crack resistance, and environmentally friendly, making it suitable for the building decoration industry.
Patent Information
- Application Number
- CN202511275377.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-08
- Publication Date
- 2025-11-28
AI Technical Summary
Existing anti-condensation coatings have poor thermal insulation effects and are prone to cracking, failing to effectively solve the condensation problem during humid weather, thus affecting the living environment and health.
The two-component coating forms a three-dimensional porous network structure through the synergistic reaction of component A and component B. Combined with modified materials and functional fillers, it achieves functions such as anti-condensation, thermal insulation, crack resistance and mildew prevention. The coating uses modified corn cob particles, modified loofah fibers and other materials to enhance moisture absorption and flexibility, and hollow vitrified microspheres and other materials to reduce heat conduction.
It achieves excellent anti-condensation performance, high moisture absorption, low thermal conductivity, high tensile bonding strength, no cracking when thickly coated, is environmentally friendly and has high resource utilization rate, and solves the problems of poor thermal insulation effect and easy cracking of traditional coatings.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of architectural finishing coatings, in particular to a dew-proof heat-insulating coating and a preparation method thereof. BACKGROUND
[0002] Back to the day is a unique humid phenomenon in southern China, when the warm and humid air flow in the environment contacts the inner wall surface of the building with lower temperature, it is easy to condense water droplets, resulting in wall "sweating", surface dew. Dew not only pollutes the wall and indoor stored goods, but also may breed mold, seriously affecting the living environment and human health.
[0003] Although the existing dew-proof coating can alleviate the dew problem to some extent, it generally has the defect of poor heat insulation effect. With the intensification of energy shortage, energy saving and emission reduction plays an increasingly important role in the development of national economy, and it is an urgent need in the current building coating field to develop an inner wall coating with excellent dew-proof performance and heat insulation performance. SUMMARY
[0004] In view of the poor heat insulation effect of the dew-proof coating in the prior art, the present application provides a dew-proof heat-insulating coating and a preparation method thereof, realizing the dual functions of "dew-proofing + heat insulation", and simultaneously considering the anti-cracking property, bonding strength and environmental protection.
[0005] The technical scheme of the present application: The application provides an anti-condensation thermal insulation coating, which is a two-component coating and comprises an A component and a B component. The application provides an anti-condensation thermal insulation coating, which is a two-component coating and comprises an A component and a B component. According to one embodiment of the application, the preparation method of the self-made soil modifier comprises the following steps: taking pure water, polyvinyl alcohol, brown rice powder, soybean powder and fresh sweet potato vine juice, mixing and heating to 95-100 DEG C, and stirring while heating for 0.8-1.2 h until gelatinization; cooling to 45-55 DEG C, slowly adding lithium water glass and calcium chloride solution, and reacting for 0.8-1.2 h after the addition is completed; cooling to 25-30 DEG C, adding mildew-proof preservative, stirring uniformly and filtering to obtain the self-made soil modifier.
[0006] The application provides a preparation method of the anti-condensation thermal insulation coating, which comprises the following steps: preparing the A component by mixing water and the self-made soil modifier and stirring uniformly at room temperature to obtain the A component; preparing the B component by mixing the modified soil mixture, sodium hexametaphosphate, sodium fluosilicate powder, light calcium carbonate, lime powder, hollow glass beads, modified corn cob particles, calcium silicate fiber powder, modified loofah fiber, color powder, borax and nano-alumina and stirring uniformly at room temperature to obtain the B component; and coating mixing by slowly pouring the B component into the A component and stirring uniformly to obtain the anti-condensation thermal insulation coating.
[0007] According to one embodiment of the application, the preparation method of the self-made soil modifier comprises the following steps: taking pure water, polyvinyl alcohol, brown rice powder, soybean powder and fresh sweet potato vine juice, mixing and heating to 95-100 DEG C, and stirring while heating for 0.8-1.2 h until gelatinization; cooling to 45-55 DEG C, slowly adding lithium water glass and calcium chloride solution, and reacting for 0.8-1.2 h after the addition is completed; cooling to 25-30 DEG C, adding mildew-proof preservative, stirring uniformly and filtering to obtain the self-made soil modifier.
[0008] According to one embodiment of the present application, the preparation method of the modified mud mixture comprises the following steps: adding lime water into dry mud, stirring uniformly; adding sodium alginate, fly ash floating bead, red brick powder, expanded perlite particles, rice husk, and continuing to stir uniformly; adding aluminum powder foaming agent, stirring, drying the mixture, and crushing to 80-100 mesh particles to obtain the modified mud mixture.
[0009] According to one embodiment of the present application, the preparation method of the modified corn cob particles comprises: cutting the corn cob into small pieces of 2-3 cm, soaking in a sodium water glass solution with a modulus of 0.8-1.2 for 0.8-1.2 h, and crushing to 80-90 mesh particles after drying.
[0010] According to one embodiment of the present application, the preparation method of the modified silk gourd fiber comprises: cutting the silk gourd into small pieces of 15-20 mm, soaking in a lithium water glass solution with a modulus of 0.8-1.2 for 0.8-1.2 h, and processing into fibers with a length of 1.5-3 mm after drying.
[0011] According to one embodiment of the present application, the hollow vitrified microsphere has a particle size of 300-500 nanometers.
[0012] According to one embodiment of the present application, the calcium silicate fiber powder is a 300-400 mesh needle-shaped structure fiber powder.
[0013] According to one embodiment of the present application, the nano-alumina has a particle size of 20-30 nanometers.
[0014] According to one embodiment of the present application, the water in the A component is pure water.
[0015] Mechanism of action of the present application: The present application realizes the comprehensive performance of "anti-condensation-thermal insulation-anti-cracking-mold prevention" through the synergistic reaction of A component (liquid material) and B component (powder material), the functional properties of modified materials, and the synergistic effect of functional fillers. The core mechanism can be divided into the following five dimensions: I. Synergistic reaction of two components: construction of three-dimensional network porous core structure After mixing A component and B component, a three-dimensional network porous structure is formed through multiple physical and chemical reactions, laying a structural foundation for anti-condensation, moisture absorption, and thermal insulation. The specific reaction path is as follows: 1. Crosslinking and fast drying reaction: the polyvinyl alcohol contained in the self-made mud modifier in A component reacts with borax in B component to crosslink, not only improving the adhesion of the coating, but also accelerating the drying of the coating; at the same time, the calcium chloride solution in A component reacts with sodium alginate in B component, further shortening the drying time and avoiding cracking or performance failure of the coating due to slow drying.
[0016] 2. Quick solidification and bonding enhancement: The sodium fluorosilicate in component B can quickly react with lithium water glass in component A to significantly improve the bonding strength of the soil base, solving the problem of weak bonding and easy peeling of traditional soil coatings; in addition, nano-aluminum oxide will react with calcium hydroxide contained in light calcium carbonate and calcium hydroxide in component B to further form micropores in the three-dimensional structure, expanding the specific surface area of the porous structure.
[0017] 3. Porous structure forming: During the preparation of the modified soil mixture, aluminum powder foaming agent reacts with calcium hydroxide in quicklime water to generate gas and form a large number of micron-sized pores; combined with the three-dimensional network structure formed by the above chemical reactions, the coating film finally presents a "large pore-mid pore-micropore" multi-level porous distribution, providing channels and space for water vapor adsorption and release.
[0018] II. Anti-condensation and humidity regulation mechanism: adsorption-release cycle controls condensation Based on the synergistic effect of three-dimensional porous structure and high-humidity materials, the coating can dynamically regulate indoor water vapor to prevent condensation during the back-south period. The specific process is as follows: 1. Quick adsorption of condensation water: During the back-south period, when warm and humid air flows contact the wall coating, the condensation water generated due to temperature difference will be quickly captured by the multi-level porous structure of the coating. Among them, the microporous structure adsorbs small molecular water vapor through capillary action, and the mesoporous / macroporous structure contains liquid condensation water; at the same time, the modified corn cob particles in component B (modified by sodium water glass, with strong humidity) and the modified silk gourd fiber (modified by lithium water glass, with both water absorption and flexibility) further enhance the humidity-adsorbing capacity, ensuring that no visible water droplets form on the coating surface (the humidity-adsorbing capacity can reach 39.5-41.3㎡ / g, which is much higher than that of traditional coatings).
[0019] 2. Water cycle release: When the environmental humidity decreases (such as the end of the back-south period or the enhancement of indoor ventilation), the water adsorbed in the porous structure of the coating will be released into the air through "gradient diffusion", making the coating return to a dry state; this "adsorption-release" cycle can be repeated, ensuring that the coating still has high humidity-adsorbing capacity when the next back-south period arrives, continuously preventing wall surface moisture and condensation.
[0020] III. Heat insulation mechanism: multi-level thermal resistance reduces heat conduction The coating builds a high-efficiency thermal resistance system through "functional filler synergism + porous structure assistance", reducing the heat conduction efficiency of the wall surface. The specific mechanism is as follows: 1. Lightweight thermal insulation synergy: Hollow glass microbeads (hollow structure breaks thermal convection and thermal radiation), fly ash floating beads (lightweight and high closed cell rate), expanded perlite particles (porous and lightweight, reducing heat conduction), calcium silicate fiber powder (forming a thermal barrier fiber network) in component B are matched in "coarse-medium-fine" particle size to form a continuous thermal barrier layer inside the coating film, reducing the transfer of outdoor cold / hot air through the wall surface.
[0021] 2. Porous structure assisted thermal insulation: The still air filled in the three-dimensional network porous structure has a much lower thermal conductivity than solid materials, which can further weaken heat conduction; at the same time, the porous structure avoids the influence of the "thermal bridge effect" of single material, making the overall thermal conductivity of the coating film as low as 0.072-0.078 w / m·k, which is better than ordinary thermal insulation coatings on the market.
[0022] Four, anti-cracking and mechanical enhancement mechanism: skeleton support + flexibility improvement Through "toughening modifier + skeleton enhancement + structure optimization", the coating solves the problem of easy cracking of traditional thick coating clay coatings, and at the same time improves the mechanical properties: 1. Flexibility and adhesion enhancement: The self-made clay modifier in component A contains millet powder, soybean powder starch and calcium chloride, which reacts to form a three-dimensional gel structure, making the starch gel strength increase by 30%-50%; polyvinyl alcohol further improves the flexibility of clay base, reduces the shrinkage stress during the drying process of the coating film, and reduces the risk of cracking.
[0023] 2. Skeleton support: Modified corn cob particles, modified loofah fiber and red brick powder in component B act as "rigid-flexible" composite skeletons, which can improve the thickness of the coating film (dry film thickness 1.5-3mm) and disperse stress. The rigid particles (red brick powder) enhance the stability of the coating film structure, and the flexible fibers (loofah) absorb the shrinkage stress to avoid cracking caused by stress concentration when thick coating.
[0024] 3. Dispersion and compatibility optimization: Sodium hexametaphosphate in component B acts as a dispersant, which can uniformly disperse modified clay mixture, lightweight calcium carbonate and other powders, avoiding mechanical property unevenness caused by local component aggregation; at the same time, the self-made clay modifier can improve the compatibility of clay and other functional fillers, further improving the overall tensile adhesion strength of the coating film (0.48-0.5MPa).
[0025] Five, antifungal and antibacterial mechanism: multiple actions to inhibit microbial growth In view of the problem that mold is easy to grow in humid environment during the hot and humid season, the coating uses "physical sterilization + chemical inhibition" dual action to prevent mold growth on the coating film and wall surface: 1. Physical sterilization: During the preparation of the modified mud mixture, the heat generated by the reaction of 15% lime water strong alkali (pH 12-13) and aluminum powder foaming agent (local temperature can reach 60-80℃) can kill the microorganisms and mold spores carried by the raw materials such as yellow mud, red brick powder and rice husk, reducing the breeding basis of mold from the source.
[0026] 2. Chemical inhibition: The calcium ions of calcium chloride in component A can damage the cell membrane structure of microorganisms and inhibit the growth of mold; at the same time, the mold-proof preservative added in the self-made mud modifier can further prolong the shelf life of the coating film (the shelf life of starch glue is prolonged by 3-4 times), avoiding the performance deterioration caused by microbial reproduction during storage and use of the coating.
[0027] The beneficial effects of the present application are: I. Excellent anti-condensation performance: The three-dimensional network porous structure formed by the coating can quickly adsorb and release water vapor. When warm and humid air flows condense on the wall surface, the condensed water is adsorbed by the coating film, and there is no surface water droplet. When the environmental humidity decreases, the coating releases water to restore dryness, which can circulate anti-condensation. There is no water droplet and moisture return phenomenon on the surface in 24h moisture-proof condensation test.
[0028] II. Good thermal insulation effect: The synergistic effect of hollow vitrified microsphere, fly ash floating bead, calcium silicate fiber powder and expanded perlite particles can reduce the thermal conductivity to 0.072-0.078 w / m·k, which is better than most existing anti-condensation coatings.
[0029] III. Strong moisture absorption capacity: Modified corn cob particles and silk gourd fiber can enhance the moisture absorption function, and the moisture absorption capacity can reach 39.5-41.3㎡ / g, which is much higher than existing coatings, and can effectively regulate indoor air humidity.
[0030] IV. Excellent mechanical properties: The tensile bonding strength is 0.48-0.5 MPa, and there is no cracking in thick coating (1.5-3 mm), which solves the problem of easy cracking and weak bonding of traditional mud coating.
[0031] V. Environmentally friendly and high resource utilization rate: Agricultural waste such as corn cob, silk gourd and rice husk is used as raw material to realize "waste to treasure", reduce resource waste and environmental pollution.
[0032] The preferred embodiments of the present application and their beneficial effects will be further described in detail in conjunction with the specific embodiments. DETAILED DESCRIPTION
[0033] The specific embodiments of the present application are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application. Example 1
[0034] 1. Coating composition A component (liquid material, parts by weight): pure water 32 parts, self-made soil modifier 68 parts; B component (powder, parts by weight): modified soil mixture 70.5 parts, sodium hexametaphosphate 1 part, sodium fluosilicate powder 1 part, 350 mesh light calcium carbonate 8 parts, 300 mesh calcium carbonate powder 4 parts, 400 nanometer hollow glass beads 3 parts, 350 mesh needle-like calcium silicate fiber powder 3 parts, modified corncob particles 5 parts, modified loofah fiber 2 parts, color powder 1 part, 20 nanometer nano-alumina 0.5 parts, borax 1 part; A:B weight ratio: 1:3.
[0035] 2. Preparation and use Preparation of A component: mix pure water with self-made soil modifier and stir uniformly; Preparation of B component: mix each powder and stir uniformly; (1) Preparation of modified soil mixture According to parts by weight, 20 parts of lime water with a concentration of 15% are added to 70 parts of dry soil (one or more of yellow soil, clay), and stirred uniformly; Add 5 parts of sodium alginate, 8 parts of fly ash floating beads of 100-200 mesh, 10 parts of red brick powder of 90 mesh, 3 parts of expanded perlite particles, and 5 parts of rice husk to the above mixture, and continue to stir uniformly; Add 5 parts of aluminum powder foaming agent, stir to make the aluminum powder foaming agent fully react with calcium hydroxide in lime water to form porous particles; Dry and crush the reacted mixture to 90 mesh particles to obtain the modified soil mixture.
[0036] The modified soil mixture has a porous structure, and the heat generated by the reaction of the strong alkalinity of lime water and the aluminum powder foaming agent can kill microorganisms and mold in the raw materials, while improving the air permeability, workability, and construction of the soil, and improving the anti-cracking and thermal insulation performance.
[0037] (2) Preparation of self-made soil modifier According to parts by weight, take 10 parts of pure water, 0.5 parts of polyvinyl alcohol, 1 part of brown rice powder, 1 part of soybean powder, and 1 part of fresh sweet potato vine juice, and add them to a reaction kettle; Heat the reaction kettle to 98℃, and stir while heating for 1h; Cool to 50℃, slowly add 3 parts of lithium water glass with a content of 20% and 2 parts of calcium chloride solution, maintain stirring during the addition process, and continue to react for 1h after the addition is completed; Cool to 28℃, add 0.5 parts of mildew-proof preservative (such as isothiazolinone, specifically 2-methyl-4-isothiazolin-3-one available on the market), stir uniformly, and filter out impurities to obtain the self-made soil modifier.
[0038] The calcium ion in the calcium chloride can form coordination with the hydroxyl group of the starch molecule, so that the gel strength of the starch glue is increased by 30%-50%, and the growth of microorganisms is inhibited, and the shelf life of the starch glue is prolonged by 3-4 times; the modifier can also improve the flexibility, anti-cracking property and bonding strength of the soil.
[0039] (3) Preparation of modified corncob particles The corncob is cut into small pieces of 2.5 cm; The small pieces of corncob are soaked in a sodium water glass solution with a modulus of 1 for 1 h; After drying, the particles are crushed to 85 mesh, and the modified corncob particles are obtained.
[0040] The modified corncob particles have both mildew-proof and moisture-proof functions and strong moisture absorption function.
[0041] (4) Preparation of modified luffa sponge fibers The luffa sponge is cut into small pieces of 18 mm in length; The small pieces of luffa sponge are soaked in a lithium water glass solution with a modulus of 1.2 for 0.8 h; After drying, the fibers are processed into fibers with a length of 2 mm, and the modified luffa sponge fibers are obtained.
[0042] The modified luffa sponge fibers have good flexibility and water absorption, and can enhance the anti-cracking function of the coating.
[0043] Coating mixing: pour the B component into the A component, stir uniformly, and spray on the cement board with a dry film thickness of 2 mm, and naturally maintain for 12 days. Example 2
[0044] 1. Coating composition A component (liquid, parts by weight): pure water 40 parts, self-made soil modifier 60 parts; B component (powder, parts by weight): modified soil mixture 66 parts, sodium hexametaphosphate 0.7 parts, sodium fluosilicate powder 0.5 parts, 400 mesh light calcium carbonate 6 parts, 300 mesh calcium oxide powder 5 parts, hollow glass beads 5 parts, 400 mesh needle-shaped calcium silicate fiber powder 4 parts, modified corncob particles 6 parts, modified luffa sponge fibers 2.3 parts, color powder 1.5 parts, 30 nanometer nano-alumina 1 part, borax 2 parts; A:B weight ratio: 1:3.5.
[0045] 2. Preparation and use Preparation of A component: mix pure water and self-made soil modifier, and stir uniformly; Preparation of B component: mix the powders, and stir uniformly; (1) Preparation of modified soil mixture Add 18 parts of lime water with a concentration of 18% into 80 parts of dry soil (one or more of yellow soil, clay), and stir well; Add 6 parts of sodium alginate, 7 parts of 100-mesh fly ash floating beads, 11 parts of 100-mesh red brick powder, 2 parts of expanded perlite particles, and 6 parts of rice husk into the above mixture, and continue to stir well; Add 4 parts of aluminum powder foaming agent, stir well, and make the aluminum powder foaming agent fully react with calcium hydroxide in the lime water to form porous particles; Dry the reacted mixture and crush it to 80-mesh particles to obtain the modified soil mixture.
[0046] The modified soil mixture has a porous structure, and the heat generated by the reaction of the alkaline of lime water and the aluminum powder foaming agent can kill microorganisms and molds in the raw materials, while improving the air permeability, workability, and construction performance of the soil, and enhancing the anti-cracking and thermal insulation performance.
[0047] (2) Preparation of self-made soil modifier Take 9 parts of pure water, 0.6 parts of polyvinyl alcohol, 0.9 parts of brown rice powder, 1.1 parts of soybean powder, and 1.1 parts of fresh sweet potato vine juice, and add them into a reaction kettle; Heat the reaction kettle to 95℃, and stir while heating for 1.2h; Cool to 45℃, slowly add 2.8 parts of lithium water glass with a content of 22% and 1.8 parts of calcium chloride solution, keep stirring during the dropping process, and continue to react for 0.8h after the dropping is completed; Cool to 25℃, add 0.4 parts of mildew-proof preservative, stir well, and filter out impurities to obtain the self-made soil modifier.
[0048] The calcium ions in the calcium chloride can form coordination with the hydroxyl groups of the starch molecules, which can increase the gel strength of the starch glue by 30%-50%, and inhibit the growth of microorganisms, prolonging the shelf life of the starch glue by 3-4 times. The modifier can also improve the flexibility, anti-cracking property, and bonding strength of the soil.
[0049] (3) Preparation of modified corn cob particles Cut the corn cob into small pieces of 2cm; Soak the small pieces of corn cob in a sodium water glass solution with a modulus of 0.8 for 1.2h; Dry and crush the removed particles to 90-mesh particles to obtain the modified corn cob particles.
[0050] The modified corn cob particles have both mildew-proof and moisture-proof functions.
[0051] (4) Preparation of modified silk gourd fiber Cut the silk gourd into small pieces of 15mm long; The small piece of loofah sponge is soaked in a lithium water glass solution with a modulus of 1.2 for 0.8 h; After being taken out, the fibers with a length of 1.5 mm are obtained by drying and processing, and the modified loofah sponge fibers are obtained.
[0052] The modified loofah sponge fibers have good flexibility and water absorption, and can enhance the anti-cracking function of the coating.
[0053] Coating mixing: pour the B component into the A component, stir uniformly, spray on the cement board, and dry film thickness is 2 mm, and naturally maintain for 12 days.
[0054] Comparative Example 1 (traditional coating without modified raw material) 1. Coating composition A component (liquid, parts by weight): water 70 parts, polyvinyl alcohol glue 30 parts; B component (powder, parts by weight): yellow clay 70 parts, 400 mesh light calcium carbonate 10 parts, 325 mesh calcium carbonate powder 5 parts, calcium silicate fiber powder 3 parts, unmodified rice husk powder 6 parts, hollow glass beads 3 parts; A:B weight ratio: 1:3.
[0055] Coating mixing: pour the B component into the A component, stir uniformly, spray on the cement board, and dry film thickness is 2 mm, and naturally maintain for 12 days.
[0056] Comparative Example 2 (commercial thermal insulation coating) A commonly used thermal insulation coating on the market is selected to be sprayed on the cement board, and the dry film thickness is 2 mm, and naturally maintained for 12 days.
[0057] The following properties are tested according to national standards, and the test results are shown in the following table.
[0058] Test method explanation Moisture-proof condensation: place the cement board coated with the coating in a sealed container, continuously pass water vapor for 24 h, and observe the surface water droplets; Anti-cracking: artificially observe the surface of the sample after coating and curing; Tensile bonding strength: tested according to JC / T2078-2011 standard; Thermal conductivity: tested according to GB / T10294-2008 standard; Moisture absorption: according to ISO24353-2008 and NORDTEST, the sample is dried to constant weight, then absorbs moisture at 23℃, 80%RH for 12 h, and then releases moisture at 30%RH for 12 h, and the moisture absorption is calculated.
[0059] The above merely preferred embodiments of the present application and are not intended to limit the present application, and any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A heat-insulating coating for preventing condensation, characterized in that, The coating is a two-component coating, comprising component A and component B, wherein the weight mixing ratio of component A to component B is 1:(2.5-3.5). Component A contains the following raw materials in parts by weight: 30-40 parts water and 60-80 parts self-made soil modifier; Component B comprises the following raw materials in parts by weight: 70-80 parts modified clay mixture, 1-1.5 parts sodium hexametaphosphate, 0.5-1.5 parts sodium fluorosilicate powder, 5-10 parts 300-400 mesh light calcium carbonate, 3-5 parts 300-400 mesh gray calcium powder, 3-5 parts hollow vitrified microspheres, 4-6 parts modified corn cob granules, 3-5 parts calcium silicate fiber powder, 2-3 parts modified loofah fiber, 1-2 parts color powder, 1-2 parts borax, and 0.5-1 parts nano alumina. The self-made soil modifier comprises, by weight: 9-11 parts purified water, 0.4-0.6 parts polyvinyl alcohol, 0.9-1.1 parts brown rice flour, 0.9-1.1 parts soybean flour, 0.9-1.1 parts fresh sweet potato vine juice, 2.8-3.2 parts 18%-22% lithium silicate, 1.8-2.2 parts calcium chloride solution, and 0.4-0.6 parts anti-mold and preservative agent; The modified soil mixture comprises, by weight, 18-22 parts of quicklime water with a concentration of 12%-18%, 70-80 parts of dried mud, 4-6 parts of sodium alginate, 7-9 parts of fly ash cenospheres of 100-200 mesh, 9-11 parts of red brick powder of 80-100 mesh, 2-4 parts of expanded perlite particles, 4-6 parts of rice husks, and 4-6 parts of aluminum powder foaming agent.
2. The method for preparing the anti-condensation thermal insulation coating according to claim 1, characterized in that, Includes the following steps: (1) Preparation of component A: Mix water with self-made soil modifier and stir evenly at room temperature to obtain component A; (2) Preparation of component B: The modified soil mixture, sodium hexametaphosphate, sodium fluorosilicate powder, light calcium carbonate, gray calcium powder, hollow vitrified microspheres, modified corn cob particles, calcium silicate fiber powder, modified loofah fiber, color powder, borax and nano alumina are mixed and stirred evenly at room temperature to obtain component B. (3) Coating mixing: Slowly pour component B into component A while stirring evenly to obtain the anti-condensation thermal insulation coating.
3. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The preparation method of the self-made soil modifier includes the following steps: (1) Take purified water, polyvinyl alcohol, brown rice flour, soybean flour and fresh sweet potato vine juice, mix them and heat to 95-100℃, stirring while heating for 0.8-1.2h until gelatinized; (2) Cool down to 45-55℃, slowly add lithium water glass and calcium chloride solution, and let the reaction proceed for 0.8-1.2h after the addition is complete; (3) Cool down to 25-30℃, add anti-mildew and anti-corrosion agent, stir evenly and filter to obtain self-made soil modifier.
4. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The method for preparing the modified soil mixture includes the following steps: (1) Add quicklime water to the dry soil and stir well; (2) Add sodium alginate, fly ash cenospheres, red brick powder, expanded perlite granules, and rice husks, and continue to stir until evenly mixed; (3) Add aluminum powder foaming agent, stir, dry the mixture and crush it into 80-100 mesh particles to obtain modified soil mixture.
5. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The method for preparing the modified corn cob particles includes: cutting corn cobs into small pieces of 2-3 cm, soaking them in a sodium silicate solution with a modulus of 0.8-1.2 for 0.8-1.2 h, drying them, and then pulverizing them into particles of 80-90 mesh.
6. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The method for preparing the modified loofah fiber includes: cutting the loofah into small segments of 15-20 mm, soaking them in a lithium water glass solution with a modulus of 0.8-1.2 for 0.8-1.2 h, drying them, and then processing them into fibers with a length of 1.5-3 mm.
7. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The hollow vitrified microspheres have a particle size of 300-500 nanometers.
8. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The calcium silicate fiber powder is a 300-400 mesh needle-like fiber powder.
9. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The particle size of the nano-alumina is 20-30 nanometers.
10. The anti-condensation thermal insulation coating according to claim 1, characterized in that, The water in component A is purified water.
Citation Information
Cited By
Diffuse reflection anti-condensation interior wall dry powder coating capable of protecting eyesight and preparation method of diffuse reflection anti-condensation interior wall dry powder coating
CN122234664A